Hubungan Antara Motivasi Terhadap Perilaku Pencegahan Human Immunodeficiency Virus (HIV) pada Pekerja Seks Komersial (PSK) di Lagoa Jakarta Utara Tahun 2019 - Nadia Dara Tamara Saputri; Murtiningsih Murtiningsih (Journal of Bionursing, 2020)
The phenomena of the increase and dissemination of cases Human Immunodeficiency Virus (HIV) that occurs in high-risk groups is very fast. One population that can be infected with HIV is CSW. This research aims to determine the relationship between motivation with prevention behavior of human immunodeficiency virus (HIV) in commercial sex workers (CSW) at Lagoa North Jakarta in 2019. The sample of this research is 49 respondents using the Accidental Sampling method. This research method is Study Correlation using the Cross-Sectional approach. The researcher uses a questionnaire to collect data and uses a Chi-Square analysis test to analyze data. The results of the univariate analysis showed that 55,1 % of respondents were highly motivated category and 71,4 % of respondents good preventive behavior categories. The results of the Chi-Square analysis test concluded that there was a significant relationship between motivation and prevention behavior of the prevention of human immunodeficiency virus (HIV) in commercial sex workers (CSW) with a value (p = 0.001). The recommendations of this research to respondents for carrying out HIV prevention and to community nurses to education or counseling related to the importance of HIV prevention.